An Analysis of Second-Year English Department Students’ Ability in Using Subordinate Conjunctions - Widy Asti; Witri Oktavia (Journal of English Language Teaching, 2019)
This research aimed to know the students’ ability and their difficulties in using subordinate conjunctions. This research is descriptive quantitative research. The population in this research is second-year students of English Department at Universitas Negeri Padang. The sample was taken by using simple random sampling. There are at 33 students that become the sample of the research. In this research, the data were collected through the grammar test. Each students were asked to answer all questions by appropriate subordinate conjunctions. The data were scored in general and every part of the test to check the quality of the students’ ability in using subordinate conjunctions. The data collected and analyzed were categorized. Then, the researcher calculated the mean score of the students to determine the students' ability in using subordinate conjunctions for overall and each part. To knowing the students’ difficulties, the data were calculated the mean score of each part, it can be interpreted by the criteria. In this research, it was found that the second year students’ ability in using subordinate conjunctions at English Department of Universitas Negeri Padang is fair because the average score of the students is 57,33. The students have good ability in answering question part. It was also found that the students have some difficulties in answering the question in part 1. It is difficult for them to decide what types of subordinate conjunctions that agree with the sentences based on its meaning.